DU KAN IKKE TALE OM DAS BECKWERK; DU ER ALLEREDE I DAS BECKWERK - Das Beckwerk, Den navnløse tidligere leder af (K&K - Kultur og Klasse, 2013)
YOU CAN’T TALK ABOUT DAS BECKWERK; YOU ARE ALREADY IN DAS BECKWERK | Subjected to a one-year ban on performances in the public spaces of Scandinavia, the former CEO of the Copenhagen-based enterprise Das Beckwerk held a lecture on 9th December 2011 solely for the ears of the rising star of fictionality and narratology Richard Walsh from the University of York. The lecture dealt not only with the disappearing boundaries between reality and fiction but also with how novel characters have become legal citizens, while the author is turned into fiction. Finally the former CEO dismisses the judgment in the famous trial “Thomas Skade-Rasmussen Strøbech versus Gyldendal and Helge Bille Nielsen”. He calls it unjust and a neglect of the fictional character’s right to a personal name, story and picture.